The effect of angle of attack and depth on passive drag - Pease, D.; Vennell, R. (Biomechanics and Medicine in Swimming XI, 2010)
Introduction: Previous research into the drag forces (both active and passive) acting during human swimming has shown differences due to body size, shape, velocity and depth. However, one factor, which has not previously been investigated, is that of the angle of attack or pitch angle of the athlete`s body relative to the water flow. Angle of attack is a factor, which has been highlighted as an issue in previous study but due to the inability to systematically control this factor it has been generally described as a limitation. Therefore, the present study was undertaken to try and quantify the effect of angle of attack on the drag forces acting upon a streamlined human swimmer by utilising an anatomically accurate mannequin whose orientation relative to the water flow direction could be precisely controlled. It was hypothesized that, as angle of attack changed, there would be significant changes in the magnitude of the total drag force as well as changes in the relative contribution of the component forces, viscous, form, and wave drag. These changes would be primarily due to the changes in exposed frontal area with increasing (positive and negative) angles of attack away from the zero angle. Based on the findings from previous research (Vennell, Pease, & Wilson, 2006) there are increases in the total drag force, and more specificlly the wave drag contribution to that total force, as depth of the swimmer decreases. Therefore, another aspect of the current study was to examine the interaction between angle of attack and submergence depth and the measured drag force. Previous studies have quantified body angles similar to angle of attack during free surface swimming (Zamparo, 2006; Zamparo et al., 2008) with the aim of using that angle as an indicator of body position. In general the angle of the trunk to the horizontal is used to represent angle of attack. In those studies body angles of approximately 15 degrees were found. However, during the streamlined portion of a swimming race when the athlete is fully submerged, and not moving on a fluid boundary, it was theorised that the angle of attack would be much less due to the freedom of the athlete`s body to move in the vertical as well as the horizontal plane. This is unlike surface swimming where the movement trajectory is fixed and essentially limited to the horizontal plane. By allowing for movement in the vertical plane as well as the horizontal, the trajectory of the centre of mass is more in line with the angle of the body thereby reducing the angle of attack relative to the surrounding water flow.Therefore, the current study examined smaller angles of attack which may be achieved by fully submerged swimmers in a streamline position such as that experienced following starts and turns.